BRIDGING THE GAP: STRATEGIC MANAGEMENT APPROACHES TO ENHANCE EDUCATIONAL QUALITY VIA TEACHER AND STAFF MANAGEMENT UNDER IASP 2020 - Badrudin, Muhamad Badar; Nugraha, Mulyawan Safwandy (Universitas Nurul Jadid, 2024)
This study aims to bridge the gap between theory and practice by examining the strategic management approach applied to improve the quality of education through teacher and staff management under the IASP 2020 framework at the madrasah tsanawiyah level. Using qualitative methods, this study collected data through in-depth interviews and participant observation. The findings of this study revealed that strategic management significantly improved the quality of education by encouraging professional development among teachers and staff, improving their managerial and pedagogical skills. This improvement was directly correlated with increased student achievement and engagement. However, this study also identified challenges such as resource constraints and resistance to change, suggesting that continuous capacity building and adaptive policy adjustments are essential. This study contributes to the existing literature by providing practical insights into effective strategic management in education, emphasizing the need for continued support from policymakers to ensure successful implementation. The findings are expected to offer a model for other schools aiming to improve educational outcomes through strategic human resource management.